2011
DOI: 10.1001/archsurg.2010.328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race and Socioeconomic Status in the Treatment of Appendicitis in Patients With Equal Health Care Access

Abstract: Lower socioeconomic background and minority race/ethnicity did not correlate with higher AP rates or a clinically longer LOH in patients with equal access to care. Based on these findings, we believe that equal health care access leads to equivalent outcomes in all patients with appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…24-26 However, these studies into impaired access and perforation have not produced consistent results. For instance, Pieracci et al, 27 Boomer et al, 14 and Lee et al 28 all found that, compared with white adults, other racial and ethnic groups had lower or similar odds of perforation (as did the current study). Moreover, many studies in the pediatric literature contradict one another in terms of which races or ethnicities have higher or lower proportions of perforation.…”
Section: Discussionsupporting
confidence: 70%
“…24-26 However, these studies into impaired access and perforation have not produced consistent results. For instance, Pieracci et al, 27 Boomer et al, 14 and Lee et al 28 all found that, compared with white adults, other racial and ethnic groups had lower or similar odds of perforation (as did the current study). Moreover, many studies in the pediatric literature contradict one another in terms of which races or ethnicities have higher or lower proportions of perforation.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have assessed what factors account for differences in LOS after appendectomy across ethnicity in both adult [25] and pediatric [26] patients, but the relationship between ethnicity and LOS remains unclear in the literature. Differences may be attributed to culture differences, home dynamics, and socioeconomic factors, but future work is necessary to clarify exactly what factors influence LOS across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Within pediatric surgery, study of appendicitis outcomes in children has identified increased incidences of perforation in black and Hispanic children compared to children of white race, a difference not explained by measurable factors within the Healthcare Cost and Utilization Project database[30]. While it has been suggested that equal access to care eliminates disparities in outcomes for patients with appendicitis, this and other studies suggest multi-factorial influences within race-related healthcare disparities[1, 31]. In addition to access limitations, developmental genetics and environmental influences have been suggested as potential factors involved in race-related disparities in the analysis of surgical site infections and each merit consideration in the assessment of race and healthcare outcomes[32].…”
Section: Discussionmentioning
confidence: 99%